Ethylene-vinyl acetate detector exposed to gamma radiation and evaluated via principal component regression - Lucas N Oliveira; Eriberto Nascimento; Patricia de Lara Antonio; Linda V.E. Caldas (Brazilian Journal of Radiation Sciences, 2022)
Ethylene-vinyl acetate (EVA) is the flexible plastic material commonly used in industries. The EVA samples, in green, white and black colors were irradiated with absorbed doses of 0.01 kGy up to 10.0 kGy using a 60Co Gamma Cell-220 system, and the Fourier Transform Infrared (FTIR) spectrophotometry technique was used for evaluating the samples. This work aimed to investigate EVA samples in measurements with gamma radiation, analyzing the linearity through the Principal Component Regression (PCR) method and its sensitivity. For sensitivity and linearity, the green samples showed the best results, followed by white and black EVA samples. The PCR method inflated gradually the number of principal components, then reducing the residuals between the measured and calculated values, consequently obtaining maximum linearity of 1.000 for all EVA samples. In conclusion, the FTIR was adequate for the acquisition of absorbance spectra, the linearity via PCR and sensitivity showed good results indicating that the EVA detectors can be useful in radiation measurements.